(untitled) (Research, Society and Development, 2021)
Introduction: The use of personal protective equipment (PPE) by motorcyclists is of great importance for the prevention of the consequences of accidents. Policies in Brazil emphasized the need to use such equipment. The aim of the study was to estimate the frequency and association of PPE use among motorcyclists and to provide advice on proper use. Methods: A cross-sectional study was conducted with a sample of 1516 motorcyclists in the metropolitan region of Recife, Brazil, between July 2014 and June 2015. A questionnaire was carried out on gender, age, acceptance of alcohol test, use of PPE and motorcycle. The ANOVA inferential statistics and Tukey’s post-hoc test were used. Results: 96% of the sample of motorcyclists were male. Helmets, shoes and jackets were the most used PPE. 92% of the sample agreed to hear advice about the use of PPE. Significant associations were found between age and individuals who heard the advice about the importance of PPE, as well as between the number of PPE used and the engine capacity of the motorcycle. Conclusion: The findings emphasize the importance of the use of PPE, which are mandatory according to Brazilian legislation.